Undergraduate Student’s Perception of HIV/AIDS.A Case of Obafemi Awolowo University Ile-Ife, NIGERIA - Okumdi Muoghalu, Caroline; O. Afolabi, Temitope (Journal of Clinical Research In HIV AIDS And Prevention, 2016)
Perception of Human Immunodeficiency Virus has been topical due to its central place in determining attitudes and care for people living with HIV/AIDS and having implications for the containment of the epidemic. People living with HIV/AIDS face social stigmatization due partly to misconception in the perception of the disease and people living with it and students are not left out in this stigmatization and discrimination. This study aimed at exploring the perception of HIV/AIDS by the students of Obafemi Awolowo University. The study utilized quantitative methodology –questionnaires to elicit information from 160 students on their perception of the disease. The sampling technique was quota sampling technique in which 40 students were randomly selected from each hostel out of the 4 selected hostels. The findings were that majority of the respondents view the disease and people living with it negatively (53.9) and dangerous (30.9) and 66.4 percent of the respondents did not see themselves being vualnerable to contracting the virus. The result further showed a significant association between knowledge and perception of the disease. It was also revealed that there was no significant relationship between perception of the disease and socio-economic status of students. This negative perception has serious implications for students living with HIV/AIDS in the University. In conclusion, the negative students’ perception of the disease and people living with it has serious implications for the containment of the epidemic in that people living with HIV/AIDS would hide their sero-positive status to avoid stigma and would in turn infect others. There is therefore need for intervention to change student perception to positive in the university.
Keywords: HIV/AIDS; perception; stigmatization and students.